The Relationship between Introvert and Extrovert Personality Types and Stress Levels in the Class of 2020 Students, Faculty of Medicine, Universitas Prima Indonesia - Zakiyyah Qurrota’aini; Wika Hanida; Isnanta, Rahmad (Community Medicine and Education Journal, 2024)
Personality is defined as the overall pattern of thoughts, feelings, and behavior that is often used in terms of adaptation to life. So that certain people can handle stress problems they have experienced for years by resolving threatening problems and situations, both behaviorally and cognitively. This study aims to determine the relationship between introvert and extrovert personality types and stress levels in students in the class of 2020, Faculty of Medicine, Universitas Prima Indonesia. The research was conducted in July-September 2023. The type of research is descriptive observational. The population covered in the study were students from the 2020 class of the Faculty of Medicine, Universitas Prima Indonesia, totaling 63 samples using purposive sampling techniques. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using tests of Chi-square data processing using the computerized IBM version 25.0 SPSS program. More than half of the students of the 2020 class of the Faculty of Medicine, Universitas Prima Indonesia have an introverted personality type, namely 42 people (66.7%), almost half of the students of the 2020 class of the Faculty of Medicine, Universitas Prima Indonesia have a moderate level of stress, namely 25 people (39.7%) and there are relationship between introverted personality type and moderate stress levels in 2020 students at the Faculty of Medicine, Universitas Prima Indonesia (p=0.004). There is a relationship between introvert and extrovert personality types and stress levels in students in the class of 2020, Faculty of Medicine, Universitas Prima Indonesia.